"Crisis", "Crime", and the Power to Heal: A Content Analysis of Online Canadian News Articles Regarding a National Inquiry on Missing and Murdered Aboriginal Women - Joubert, Tara L. S.; Perkins, Charmaine (Author) (2015)
content analysis qualitative research Aboriginal women Canadian online news missing murdered national inquiry news articles media representations Indigenous First Nations Over the past four years, the call for a national inquiry on missing and murdered Aboriginal women in Canada has grown in momentum. After several highly publicized murders and the recent release of a Royal Canadian Mounted Police report, the topic of missing and murdered Aboriginal women has garnered considerable media attention. Thus, the purpose of this descriptive study is to examine how the issues surrounding the call for a national inquiry on missing and murdered Aboriginal women have been represented in online Canadian news between 2010-2014. Employing content analysis on news articles from four online news websites, the results indicated that issues were framed through a model of conflict between opposing sides. International and domestic advocates framed the inquiry as a need for justice, while the opposing federal government suggested it was redundant. Qualitative Research Methods 3104 2014-12-01T00:00:00Z